Message embedding technique in Elliptic Curve Cryptography using multiple of points / Nur Syafawani Mat Syet, Ummi Afifah Mohamad Arsad and Muhammad Faiz Abdul Shukor - Mat Syet, Nur Syafawani; Mohamad Arsad, Ummi Afifah; Abdul Shukor, Muhammad Faiz (2019)
Public key cryptosystem is a famous technique that has been developed by using elliptic curve. In this paper, a method of embedding plaintexts is proposed in binary field, GF (2 5 ); it is irreducible polynomial and satisfies condition b ≠ 0. Maple 2016.1 is used to show how the encryption and decryption works. Thus, a method is implementing into MVECC protocol successfully based on encryption and decryption.